Effect of a Structured Teaching Module Including Intensive Prophylactic Measures on Reducing the Incidence of Capecitabine‐Induced Hand‐Foot Syndrome: Results of a Prospective Randomized Phase III Study. (4th September 2020) - Ostwal, Vikas; Kapoor, Akhil; Mandavkar, Sarika; Chavan, Neeta; Gupta, Tarachand; Mirani, Jimmy; Saklani, Avanish; Desouza, Ashwin; Murugan, Kalaivani; Nashikkar, Chaitali; Gupta, Sudeep; Ramaswamy, Anant
Abstract: Lessons Learned: A structured teaching module including intensive prophylactic measures to alleviate hand‐foot syndrome (HFS) during capecitabine therapy is feasible but ineffective at protecting patients from HFS. Pharmacologic therapeutic interventions should be investigated for the management of this complication. Background: Capecitabine‐induced hand‐foot syndrome (HFS) has a detrimental effect on quality of life. The effect of a structured teaching module including intensive prophylactic measures was evaluated. Methods: This non‐crossover phase III double‐blinded clinical trial randomized patients in a 1:1 ratio to either a control group or to a group administered a structured teaching model including intensive prophylactic measures on HFS administered by a trained oncology nurse at regular intervals (case) versus standard information on HFS care administered by treating clinician (control). The primary endpoint was comparison of fraction of patients in both arms developing at least grade 2 HFS. Results: Between June 15, 2016, and April 4, 2018, 280 patients (140 to case and 140 to control) were enrolled. The median number of capecitabine chemotherapy cycles was eight; 269 patients (96%) were evaluable for HFS, of whom 89 patients (33.08%) developed at least grade 2 HFS (grade 2 HFS, 73 patients [26.1%]; grade 3 HFS, 16 patients (5.7%